Radiocarbon Chronology of Prehistoric Campsites in Alpine and Subalpine Zones at Haleakalā, Maui Island, USA. Issue 2 (18th July 2016) - Carson, Mike T; Mintmier, Melanie A
Abstract : A chronological synthesis of prehistoric campsites in alpine and subalpine zones (∼2–3 km asl) at Haleakalā, Maui Island, USA, is based on relative stratigraphy from 24 test excavations, associated artifacts of known or probable time periods, and 12 radiocarbon dates. The results indicate intensive use of the unfavorable high-altitude environment in the range of AD 1400–1600, with very limited use slightly earlier. Numerous campsites were used repeatedly near the Haleakalā crater rim and scattered on the lower western mountain slope. Prior to this time, activity in this inhospitable setting was infrequent and occurred on a small scale.